Distribution of larval and juvenile pelagic squids in the Kerguelen Axis region: Oceanographic influence on size structure and evidence of spawning locations. (April 2020) - Lin, Dongming; Walters, Andrea; Bestley, Sophie; Zhu, Guoping; Chen, Xinjun; Trebilco, Rowan
Abstract: Pelagic squids are a key component in Southern Ocean ecosystems. Most species have a circumpolar distribution that is patchy in relation to major oceanographic features. However, little is known regarding where and when they spawn, or subsequently, what environmental predictors drive the size distribution particularly during early life stages. Here, we relate the size distribution of larval and juvenile squids to the oceanographic conditions around the southern Kerguelen Plateau. This is an important foraging area for many predators of squid, but there has been very little sampling effort for squids to date in that area. Seven squid species from six families were captured using depth-stratified mid-water trawls. The squids had a mantle length (ML) ranging from 7.3 to 680.1 mm, and were at their larval and juvenile form with the exception of two larger mature Galiteuthis glacialis (431.4 mm and 680.1 mm ML). Squids at stages 0 to I were predominant (ML < 100 mm), with a single size mode for each species, suggesting that these species may use the plateau as a spawning and/or nursery ground. Larger individuals (>100 mm ML, above maturity stage I) were generally observed more in the southeast of the study domain. Squid size was positively associated with lower minimal water column temperature, higher surface chlorophyll- a concentration, and both the deepest and shallowest layers of the water column. The spatial distribution may be adaptive, helping to reduce inter- and intra-species competition and increase survivorship during early life stages. The reported relationships provide important new insights into the biophysical drivers of pelagic squid habitats around the Southern Ocean. These data significantly increase the known range of several Southern Ocean species and present implications for spawning habitat that warrant further investigation.